2017
DOI: 10.1002/adsc.201701304
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of γ‐ and δ‐Keto Esters into Optically Active Lactams. Transaminases in Cascade Processes

Abstract: A one-pot two-step enzymatic strategy has been designed for the production of optically active gand d-lactams in aqueous medium under mild conditions. The approach is based on the biotransamination of ethyl or methyl keto esters bearing different alkyl or aryl substitution patterns at a-position to the ketone functionality. In this manner, the keto esters were transformed into the corresponding amino esters with excellent conversions, which underwent spontaneous cyclisation in the reaction medium without addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 28 publications
0
22
1
1
Order By: Relevance
“…In the case of β‐amino acids, additional enzyme i. e. lipase needs to be added for the hydrolysis of ester substrates . As, ATAs used in this study do not show reactivity towards β‐keto esters, β‐keto acids were used as substrates for the synthesis of corresponding β‐amino acids.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of β‐amino acids, additional enzyme i. e. lipase needs to be added for the hydrolysis of ester substrates . As, ATAs used in this study do not show reactivity towards β‐keto esters, β‐keto acids were used as substrates for the synthesis of corresponding β‐amino acids.…”
Section: Methodsmentioning
confidence: 99%
“…Gotor‐Fernández et al reported a related transamination, using γ ‐ and δ ‐keto esters. The ketone is reduced by a transaminase (Scheme ) and the cyclization of the resulting amino esters result in γ ‐ and δ ‐ lactams . The use of amino alcohols has been recently reported in the synthesis of β ‐, γ ‐ or δ ‐lactams, in a bienzymatic cascade …”
Section: Enabling Technologymentioning
confidence: 99%
“…the cyclization of the resulting amino esters result in γand δlactams. [14] The use of amino alcohols has been recently reported in the synthesis of -, γor δ-lactams, in a bienzymatic cascade. [15] Scheme 9.…”
mentioning
confidence: 99%
“…The use of organic cosolvents improves the substrate solubilisation in ATA-catalysed transformations, favouring higher reaction conversion values as the enzyme activity is usually completely maintained at low volumes of organic solvent (typically DMSO, DMF or MeCN) [33] and, besides, showed a beneficial effect on the Wacker-Tsuji step. For this reason, MeCN (2.5-10% v/v) was selected for further optimisation of the biotransamination experiments over ketone 2 a (Table 4).…”
Section: Full Paper Ascwiley-vchdementioning
confidence: 99%